2020
DOI: 10.1007/s13555-020-00360-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of NUDT15 Variants on Neutropenia Among Han Chinese Patients with Dermatologic Diseases: A Single-Center Observational Study

Abstract: Introduction: Azathioprine is a synthetic purine analogue derived from 6-mercaptopurine which acts by disrupting nucleic acid synthesis and interfering with T cell activation. It is effective in dermatology diseases related to the immune system. However, its side effects, including severe neutropenia, kept patients from using it. Mutations in thiopurine methyltransferase (TPMT) and inosine triphosphate pyrophosphohydrolase (ITPA) genes account for the major genetic polymorphism markers for azathioprine adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(46 reference statements)
2
4
0
Order By: Relevance
“…The frequency of NUDT15 mutations in IBD patients in Japan and South Korea is 12% and 10.4%, respectively, but it can be as high as 32.1% in Chinese patients with autoimmune diseases 31 . The frequency observed in this study was 12.4%, which is similar to the frequency of 9.4% in patients with AIH reported by Xiaoli Fan et al 19 Recent studies have found that NUDT15 c.415C > T variants were associated with thiopurine-induced leukopenia, particularly in Asian populations 28 , 32 34 . In 2014, Yang et al 11 revealed that NUDT15 c.415C > T allelic mutation is significantly associated with AZA-induced leukopenia in Korean IBD patients ( P = 5.58 × 10 −43 , OR = 8.61).…”
Section: Discussionsupporting
confidence: 88%
“…The frequency of NUDT15 mutations in IBD patients in Japan and South Korea is 12% and 10.4%, respectively, but it can be as high as 32.1% in Chinese patients with autoimmune diseases 31 . The frequency observed in this study was 12.4%, which is similar to the frequency of 9.4% in patients with AIH reported by Xiaoli Fan et al 19 Recent studies have found that NUDT15 c.415C > T variants were associated with thiopurine-induced leukopenia, particularly in Asian populations 28 , 32 34 . In 2014, Yang et al 11 revealed that NUDT15 c.415C > T allelic mutation is significantly associated with AZA-induced leukopenia in Korean IBD patients ( P = 5.58 × 10 −43 , OR = 8.61).…”
Section: Discussionsupporting
confidence: 88%
“…There were 1,167 cases with leukopenia and 240 cases with neutropenia. Among these, 14 studies were conducted in IBD (Yang et al, 2014;Asada et al, 2016;Kakuta et al, 2016;Zhu et al, 2016;Chao et al, 2017;Sato et al, 2017;Shah et al, 2017;Kakuta et al, 2018a;Sutiman et al, 2018;Wang et al, 2018;Akiyama et al, 2019;Banerjee et al, 2020;Kang et al, 2020;Xu et al, 2020), nine studies in ALL (Tanaka et al, 2015;Chiengthong et al, 2016;Tanaka et al, 2018;Zhou et al, 2018;Buaboonnam et al, 2019; Choi et al, 2019;Kodidela et al, 2020;Puangpetch et al, 2020;Ramalingam et al, 2021) and seven studies in other autoimmune diseases (autoimmune hepatitis, dermatological diseases and rheumatological diseases) (Kim et al, 2017b;Fei et al, 2018;Yang et al, 2019a;Fan et al, 2019;Huang et al, 2020;Su et al, 2020;Miao et al, 2021). Myelosuppression was categorized based on the onset and characteristics of blood cell type, including of leukopenia and neutropenia.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…We and another group have ever reported two cases of PV with NUDT15 mutation developing leukopenia following AZA treatment 13,14 . Recently, a study from dermatology also reported pretreatment screening of NUDT15 might reduce the chance of AZA‐induced hematological adverse effects in Han Chinese 15 . These findings underscore the necessity of pretesting TPMT and NUDT15 mutations and adjust AZA dose according to genetypes during AZA treatment in Asia including China.…”
Section: Discussionmentioning
confidence: 83%
“…13,14 Recently, a study from dermatology also reported pretreatment screening of NUDT15 might reduce the chance of AZA-induced hematological adverse effects in Han Chinese. 15 These findings underscore the necessity of pretesting TPMT and NUDT15 mutations and adjust AZA dose according to genetypes during AZA treatment in Asia including China. The latest general guidelines for prescribing thioprine were reported in 2018.…”
Section: Discussionmentioning
confidence: 89%